Synchronous and Asynchronous Collaborative Dynamics and Strategies in an Online University Using Digital Tools - Mosquera Gende, Ingrid (International Journal of Information and Education Technology, 2025)
This article analyzes the results of an innovative experience that took place in an online university in Spain, with the aim of finding the best strategies, dynamics and digital tools to encourage synchronous and asynchronous student participation. For this purpose, students from the Bachelor’s Degree in Early Childhood Education and students from the Master’s Degree in Secondary Education voluntarily and anonymously answered a pre-tested questionnaire. The sample was made up of a total of 69 students, 33 from the bachelor’s degree and 36 master’s students. The results have confirmed that students prefer to work in small groups and that they appreciate complementary activities in order to continue learning and to improve their digital competence. With specific reference to digital tools, those that allow collaboration and those that foster autonomy and a sense of belonging to a group are the ones most highlighted by students. Also noteworthy are the tools that allow students to leave contributions both during the live classes and later in recorded classes, facilitating the participation of all the students and the possibility of reflecting in a calm manner before making contributions. Finally, it has been shown that there is a need to continue searching for better strategies so that students who watch the recorded classes can take advantage of the time and enjoy the group activities done by their classmates in a synchronous way.
Keywords: online education; collaborative learning; digital tools; educational technology; interaction